The impact of gender inequality on economic development - Ongezwa Ndzabela; Yusuf Lukman (Insights into Regional Development)
Gender inequality in employment remains a significant challenge in many countries, including South Africa. The impact of this inequality on economic development is a topic of increasing interest and concern, with many studies showing a correlation between gender equality and economic growth. This study explores the impact of gender inequality in employment on economic development in South Africa, with a case study of Nyandeni local municipality. The study employs a quantitative, statistical technique to answer the study issues. The article explores the challenges faced by women in the workforce, the impact of gender employment equity policies, and the role of government, businesses, and civil society in addressing gender inequality in employment and promoting economic development within Nyandeni Local Municipality. This research seeks to determine if women's work will provide an extra lever for economic expansion. A fundamental study on women's involvement in economic development describes the position of women in Africa, Asia, and Latin American nations. The theory that frames the accompanying debate focuses on inequalities, growth, gender, and capacities in general, and the influence of gendered disparities on salaries, education, and economic growth. This research aims to reveal a connection between economic development in South Africa and gender equality. As a second objective, the study seeks to determine whether the contribution of women to economic growth provides extra valuable information for economic policymaking. South Africa's gender gap in employment remains despite legislative and legal progress in the battle against gender inequality.